Dentro de la Biblioteca Glo-cal: ¿usuarios, clientes o simplemente público? - Sevilla Mompó, Manuela (Revista General de Información y Documentación, 2008)
Throughout the last years we have witnessed a debate about new model of public library our society requires. The current public library is not considered as an institution of a purely cultural character, but one that must favour its revitalizing character as an element of social development and become a big centre of information for the local community; all these take us to new tasks and aims. The library can develop and foster the integration of the people in the community it serves and there are many ways of doing it. At this stage i think that if we do not stop to think about it, libraries are in danger of losing their main aims and turn into any thing, as their sphere of activity is more and more open, and although this is a positive thing, i think that everything is no good if it is not carried out with an aim or a real approach of service.
Keywords: Users of the information; New Technologies of the Information and the Communications; Documentary supports; Information services; Technological revolution; New supports; New services; New users